Three new species of the genus Scaphoideus (Hemiptera: Cicadellidae) with notes on the female of Scaphoideus varna from India - Meshram, Naresh M. (Zootaxa, 2014)
Three new species of leafhoppers, Scaphoideus ramamurthyi sp. nov. (from Meghalaya: Barapani), Scaphoideus menoni sp. nov. (from Kerala: Valluvady) and Scaphoideus viraktamathi sp. nov. (from Kerala: Kannavam) from India, are described and illustrated. Also, the female of S. varna Viraktamath & Mohan, previously known only from Myanmar is described with a new record for India. Taxonomic notes on the few cryptic species of Scaphoideus also provided.